Operating Systems (OS): An Insight Investigative Research Analysis and Future Directions - Bin Akhtar, Zarif (Universitas Dinamika, 2024)
In the realm of technological computing, the pivotal interface of operating systems (OS) governs the orchestration of machinery, orchestrating seamless human interactions with the swiftly advancing array of device peripherals. Over decades, the intricacies of computing have undergone a profound metamorphosis, embracing monumental leaps facilitated by the progressive proliferation of operating system distributions. From the erstwhile colossal processing units to the present-day intricately crafted nano-fabricated microcontrollers, motherboards, and chipsets, all human-computer interactions gravitate towards the nuanced tapestry of OS distributions and intricately woven source-coded programming. This comprehensive research endeavors to undertake a meticulous exploration of the myriad typologies of operating systems, intricately dissecting their distinctive functionalities and performance metrics, with a discerning focus on aligning specific user profiles with the most fitting OS distributions. Moreover, this investigation seeks to unravel the labyrinthine landscape of OS distributions, illuminating the optimal pathways for both seasoned users and neophytes alike.